Challenges in the Implementation of Judges' Professional Ethics and Conflicts of Interest that Affect Integrity - Bimo, Anthonio; Lie, Cathleen; Clarosa, Vivian; Christian, Juttah; Bryan, Hanz; Saly, Jeane Neltje (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
The judicial profession is a profession that has a very important role in carrying out the law enforcement process. To enforce the law, a judge is required to make a decision that will be the settlement of a case that occurs. In its implementation, the judge upholds the code of ethics that is owned to carry out a fair and correct judicial power. The implementation of professional ethics as a judge is certainly faced with many challenges. Not a few members of the judges are unsteady in upholding the code of ethics that should be followed. Integrity is needed so that there is no violation of the code of ethics.